FACTORS AFFECTING PERFORMANCE AMONG PUBLIC SERVANTS IN LOCAL GOVERNMENT AUTHORITY IN TANZANIA; A CASE STUDY OF BARIADI DISTRICT COUNCIL - Kombo, Dr. Ibun; Ijagara, Dismass (IJRDO - Journal of Social Science and Humanities Research, 2016)
This paper is focusing on factors affecting poor Performance among Public Servants on Local Government (LG) in Tanzania. This study was conducted with an intention of finding out obstacles hindering good performance among public servants in local government. The study recognized facts about Personal and Institutional factors hindering public servant in LG to improve social services delivery at the grass root as well as the strategies that will help to overcome the existing obstacles. Primary data were drawn from the observation, questionnaire and interview methods. With regards to secondary data sources; the researchers used documentation to gather information from the government sectors through reports, permitted written materials and internet services. The researchers collected data from fifteen (15) villages attained in four (4) wards namely Bariadi, Bunamhala, Somanda, and Nyakabindi. The data was collected from one hundred and five (105) respondents obtained from heads of departments Councillors, Village Executive Officers, Village Council Members and Community Members. This research signifies that there is an override of a decentralization and delegation of power at village units. The study recognized the personal and institutional challenges with personal capacity of government actors which was not satisfactory due to inadequate skills and knowledge, lack of office and its facilities, lack of funds and political intrusion as major factors among others at village level. The study used different methods for data collection including questionnaires, interviews, and focus group discussions.